The LEAD study protocol: A mixed-method cohort study evaluating the lung cancer diagnostic and pre-treatment pathways of patients from Culturally and Linguistically Diverse (CALD) backgrounds compared to patients from Anglo-Australian backgrounds - Mazza, D.; Lin, X.; Walter, F.; Young, J.; Barnes, D.; Mitchell, P.; Brijnath, Bianca; Martin, A.; Emery, J. (BioMed Central Ltd., 2018)
Background: Lung cancer is the leading cause of cancer mortality worldwide. Early diagnosis and treatment is a key factor in reducing mortality and improving patient outcomes. To achieve this, it is important to understand the diagnostic pathways of cancer patients. Patients from Culturally and Linguistically Diverse (CALD) are a vulnerable group for lung cancer with higher mortality rates than Caucasian patients. The aim of this study is to explore differences in the lung cancer diagnostic pathways between CALD and Anglo-Australian patients and factors underlying these differences. Methods: This is a prospective, observational cohort study using a mixed-method approach. Quantitative data regarding time intervals in the lung cancer diagnostic pathways will be gathered via patient surveys, General practitioner (GP) review of general practice records, and case-note analysis of hospital records. Qualitative data will be gathered via structured interviews with lung cancer patients, GPs, and hospital specialists. The study will be conducted in five study sites across three states in Australia. Anglo-Australian patients and patients from five CALD groups (i.e., Arabic, Chinese, Greek, Italian and Vietnamese communities) will mainly be identified through the list of new cases presented at lung multidisciplinary team meetings. For the quantitative component, it is anticipated that 724 patients (362 Anglo-Australian and 362 CALD patients) will be recruited to obtain a final sample of 290 (145 per group) assuming a 50% patient survey completion rate and a 80% GP record review completion rate. For the qualitative component, 60 interviews with lung cancer patients (10 Anglo-Australian and 10 patients per CALD group), 20 interviews with GPs, and 20 interviews with specialists will be conducted. Discussion: This is the first Australian study to compare the time intervals along the lung cancer diagnostic pathway between CALD and Anglo-Australian patients. The study will also explore the underlying patient, healthcare provider, and health system factors that influence the time intervals in the two groups. This information will improve our understanding of the effect of ethnicity on health outcomes among lung cancer patients and will inform future interventions aimed at early diagnosis and treatment for lung cancer, particularly patients from CALD backgrounds.